The Benefit of Cross-Modal Reorganization on Speech Perception in Pediatric Cochlear Implant Recipients Revealed Using Functional Near-Infrared Spectroscopy - Mushtaq, Faizah; Wiggins, Ian M.; Kitterick, Pádraig T.; Anderson, Carly A.; Hartley, Douglas E. H. (Frontiers in Human Neuroscience, 2020)
Cochlear implants (CIs) are the most successful treatment for severe-to-profound deafness in children. However, speech outcomes with a CI often lag behind those of normally-hearing (NH) children. Some authors have attributed these deficits to takeover of auditory temporal cortex by vision following deafness, which has prompted some clinicians to discourage the rehabilitation of paediatric CI recipients using visual speech. We studied this cross-modal activity in temporal cortex, along with responses to auditory speech and non-speech stimuli, in school-age CI users and NH controls, using functional near-infrared spectroscopy. Strikingly, CI users displayed significantly greater cortical responses to visual speech, compared with controls. Importantly, in the same regions, processing of auditory speech, compared with non-speech stimuli, did not significantly differ between the groups. This suggests that visual and auditory speech are processed synergistically in temporal cortex of children with CIs, and they should be encouraged, rather than discouraged, to use visual speech.